Mirror for Princes in Medieval Islamic Politics: Justice in the Nasihat al-Mulk Al-Ghazali - M Rizwan; Muntasir Muntasir; Dahlan A Rahman; Zulhilmi Zulhilmi (Siyasah Wa Qanuniyah, 2025)
The Mirror for Princes genre comprises works by scholars and religious figures designed to offer guidance and advice to rulers. This genre was widespread in both Europe and the Islamic world during the classical and medieval eras. In the Islamic world, these works aimed to provide moral guidance and practical advice to leaders under various titles. One notable example is Imam al-Ghazali's “al-Tibrul al-Masbuk fi Nasihat al-Mulk.” This paper employs a literature study approach to analyze the text, examining the book's manuscript to understand how scholars conveyed advice to Islamic rulers in the Middle Ages. The text can be seen as a persuasive form of political thought, offering rulers theological, ethical, and practical guidance. Al-Ghazali's manuscript on al-mulk comprises an introduction and seven chapters, addressing topics such as Sunni theology, justice and politics, the structure of ministries and the ethical conduct of their secretaries, the titles of kings, the wisdom of philosophers, the significance of reason and thinkers, and a discussion of the position of women. The existence of mirror for princes' manuscripts in the Islamic world shares similarities with political texts from the Persian and Roman empires. One of al-Ghazali's important advice to rulers is that justice is closely related to the permanence of power.